Model Good Governance Berbasis E- Government dan Motivasi Pelayanan Publik Pada Aparatur Sipil Negara Pemerintah Kota Cimahi - Romi, Mochamad Vrans (Universitas Batanghari, 2024)
Government practice in the era of the rise of artificial intelligence prioritizes e-government in its implementation, but in reality it is still not used optimally by stakeholders so that the public lacks knowledge of the existing e-government programs that are used. The lack of access to information on the official Cimahi City Government portal is also a concern where the government as a public servant must prioritize openness in providing information to the public. The aim of this research is to create a model to determine the influence of e-government and public service motivation on good governance in the civil service of the Cimahi City government, both partially and simultaneously. The methodology in this research uses descriptive analysis with quantitative methods, the research object is a sample of 98 Cimahi City Government Apparatus. The sampling method is by taking a sample of Cimahi City Government Apartments based on a simple random sampling technique from the total number of Cimahi City Government Apartments. Data analysis uses multiple linear regression, processing data using SPSS v.25 software. The results of this research show that there is a positive and significant influence of e-government and public service motivation on improving good governance in Cimahi City. It can be concluded that the higher the e-government and public service motivation, this will have an impact on improving good governance in Cimahi City, good governance accompanied by easy access to various public services for the community, especially in Cimahi City.